Pengaplikasian Media Audio Visual Dalam Pembelajaran Berbicara Bahasa Jerman (Sprechfertigkeiten) - Tarida Alvina Simanjuntak; Lydia Purba (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2023)
In learning German, vocabulary mastery is mandatory. Especially in the digital era, challenges in language learning can be answered through the application of audio-visual media. Along with that, the production of audio-visual media in teaching students has not yet been optimal, so the purpose of this activity is to introduce the production of audio-visual media to teachers in language learning and see the effectiveness of using audio-visual media in the language learning process. The method used in this activity is to include various lectures accompanied by direct practice. The results of this activity are in the form of teachers' skills in making audio-visual media, especially in language learning. Prior to this activity, there was still a very small percentage of teachers who could make and use audio-visual media in learning. It can be seen that the enthusiasm of the teachers in this activity is that ≥ 90% of the teachers have been able to make and use animated media in language learning. This is very effective in keeping students enthusiastic about participating in learning, especially in language learning.